(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Yield and yield penalty as well as economic suitability of various high yielding varieties needed to be assessed by different crop establishment methods before promoting a sustainable crop establishment method in Bangladesh. There for, an experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during November 2017 to June 2018 to study the effect of crop establishment methods on the yield and economics of boro rice. The experiment comprised of two factors; factor A: methods of crop establishment viz. dry direct seeding, unpuddle transplanting, AWD (Alternate Wetting and Drying) and puddle transplanting; factor B: rice cultivars viz. BRRI dhan28, BRRI dhan58, BRRI dhan74 and BRRI hybrid dhan3. The experiment was laid out in a split-plot design with three replications where method of crop establishment was assigned to the main plot and rice cultivar was assigned to the sub plots. The results showed that plant height, number of total tillers hill-1, effective tillers hill-1, number of grains panicle-1, grain yield, straw yield and harvest index were significantly influenced by crop establishment methods. The highest grain yield (5.54 t ha-1) was obtained in puddle transplanting method due to production of higher number of effective tiller hill-1 and higher number of grains panicle-1. Among varieties, the highest grain yield (4.80 t ha-1) was obtained in BRRI hybrid dhan3. The highest grain yield (6.21 t ha-1) was found in puddle transplanting with BRRI dhan28, while the lowest grain yield (2.80 t ha-1) was produced in dry direct seeding with BRRI dhan28. From the economic analysis it is observed that the highest BCR (benefit cost ratio) was observed in puddle transplanting with BBRI dhan28. Puddle transplanting with BRRI dhan28 might be recommended for obtaining higher grain yield and higher BCR of boro rice. J Bangladesh Agril Univ 17(4): 521–525, 2019